Hidden 19S IgM rheumatoid factor in adults with juvenile rheumatoid arthritis onset. Issue 5 (May 1985) - Speiser, J C; Moore, T L; Weiss, T D; Baldassare, A R; Ross, S C; Osborn, T G; Dorner, R W; Zuckner, J
Abstract : Forty-eight adult patients with juvenile rheumatoid arthritis (JRA) (onset before age 16 years) were evaluated at the age of 17 years or more for the presence of hidden 19S IgM rheumatoid factors (RF), i.e., 19S IgM RF that can be detected by the complement-dependent haemolytic assay in the IgM-containing fraction after separation of the serum by acid gel filtration. The average age of the patients was 25.3 years. The mean duration of disease was 16.5 years. Thirty-two of 48 patients (67%) showed the presence of hidden 19S IgM RF in their serum. Disease activity correlated with hidden RF titres in 62% (55/88) of the evaluations. The results indicate that patients with seronegative JRA onset continue to have significant titres of hidden 19S IgM RF in their sera into early adulthood.